A Tale of Two Bankruptcies: Geographic Differences in Bankruptcy Chapter Choice - Nathaniel Pattison; Daniel L. Millimet (Institute of Labor Economics (IZA), 2023)
The importance of place of birth or residence on a host of economic outcomes cannot be overstated. The treatment of households in consumer bankruptcy appears to be no different. Despite the U.S. Bankruptcy Code being federal law, there is extreme geographic variation in the relative use of the two types of consumer bankruptcy – Chapter 7 and Chapter 13 – and these differences lead to disparities in bankruptcy's balance between debt relief and creditor repayment. Guided by the legal literature, we develop a framework to decompose the geographic variation into three potential sources: (i) differences in filer characteristics, (ii) differences in how courts steer filers based on those characteristics, and (iii) differences in how frequently filers deviate from court steering. The results reveal that heterogeneity surrounding a single characteristic, disposable income, explains most of the geographic variation in chapter choice. Moreover, we show that disposable income plays an important and overlooked role in screening within the bankruptcy system, and we discuss the legal mechanisms behind this screening. Finally, we explore the consequences of improving uniformity in the bankruptcy system.
Keywords: D31; G28; G51; R59; 330; bankruptcy; chapter choice; regional disparities